PERAN PENDAMPINGAN UMKM TERHADAP PEMAHAMAN PENCATATAN KEUANGAN SEDERHANA PELAKU UMKM DI SWK TANAH MERAH - Jasmine Afianda Azahra; Siti Sundari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Writing scientific articles using qualitative methods because the use of this method can obtain descriptive results carried out during the mentoring period. In the process of writing the article, researchers conducted field observations to see the condition of MSMEs assisted by DINKOPUMDAG in the Tanah Merah Culinary Tourism Center. Researchers also conducted interviews to explore information about the role of mentoring for traders. The research subjects were MSME players in SWK Tanah Merah, the informants interviewed were 2 out of 8 traders because the two samples had represented the population. MSME assistance is very important for the understanding of simple financial recording of MSME actors because it plays a role in introducing, providing material, and implementing financial recording. Facilitators help MSMEs by providing relevant information, especially regarding simple financial records. The results of this study are that MSME actors can understand and implement simple financial records, know business profits or losses, and can classify personal assets with business assets so that they can carry out financial management properly.